2021
DOI: 10.1177/07334648211023661
|View full text |Cite
|
Sign up to set email alerts
|

Person-Centered Care in Nursing Homes: Potential of Complementary and Alternative Approaches and Their Challenges

Abstract: A person-centered approach to care shifts the mind-set of care partners from a traditional medical model to a social model in managing chronic conditions. Using a qualitative descriptive approach, this study examines the barriers and facilitators to the implementation of person-centered care (PCC) and how the integration of complementary and alternative approaches (CAA) has the potential to improve residents’ quality of life in nursing homes (NHs). Findings indicate that NHs offer a wide range of engagement ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…It is important to note that data were collected from March to July 2021, by that time, nursing homes may have overcome problems with supply and training experienced early on in the pandemic and began to develop practices to support teams of staff. COVID-19-related precautions influenced the relationships and interaction between staff, family, and residents and made it more difficult to provide choice and autonomy in terms of in-person contact for residents with their families which is key to implementing PCC (Bhattacharyya et al, 2022). However, we found that the staff discovered a viable substitute for in-person interaction.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…It is important to note that data were collected from March to July 2021, by that time, nursing homes may have overcome problems with supply and training experienced early on in the pandemic and began to develop practices to support teams of staff. COVID-19-related precautions influenced the relationships and interaction between staff, family, and residents and made it more difficult to provide choice and autonomy in terms of in-person contact for residents with their families which is key to implementing PCC (Bhattacharyya et al, 2022). However, we found that the staff discovered a viable substitute for in-person interaction.…”
Section: Discussionmentioning
confidence: 77%
“…COVID-19–related precautions influenced the relationships and interaction between staff, family, and residents and made it more difficult to provide choice and autonomy in terms of in-person contact for residents with their families which is key to implementing PCC ( Bhattacharyya et al, 2022 ). However, we found that the staff discovered a viable substitute for in-person interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care partners and convoys need supportive social environments that value time spent with care recipients on meaningful engagement during, before, after and between care activities (Bhattacharyya et al, 2022; Morgan & Ahmad, 2022). Further, stigma, or “collective cultural representation of persons living with dementia as being incapable of purposeful and meaningful communication and interaction” is a persistent barrier to social engagement, meaningful activities and social inclusion (Kontos et al, 2021, p. 714).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report by the American Health Care Association (AHCA, 2022) found that since 2022, 60% of US NHs reported experiencing worse staffing situations and 87% are facing moderate or high staffing shortages. Given the importance of staffing levels on PCC delivery (Dys et al, 2022) coupled with these recent trends, it is unsurprising that inadequate staff time (Kolanowski et al, 2015; Van Haitsma et al, 2014) and staff turnover (Bhattacharyya et al, 2021) are often cited as barriers to implementing PCC in NHs. As NHs are mandated to provide PCC by the Centers for Medicare and Medicaid Services (CMS, 2016), it is imperative to understand how NHs can do so effectively and efficiently.…”
Section: Introductionmentioning
confidence: 99%